Ureteroscopy: is it the best?. Issue 2 (April 2014) - Porpiglia, Francesco; Fiori, Cristian; Poggio, Massimiliano; Cossu, Marco; Amparore, Daniele; Manfredi, Matteo; Bertolo, Riccardo; Mele, Fabrizio; Garrou, Diletta; Cattaneo, Giovanni; Scarpa, Roberto Mario
Over the last 40 years the treatment of urolithiasis passed from open surgical therapies to minimally invasive approaches. From the introduction of the first ureteroscopes in '80s many technological improvements allowed to reduce endourological instruments' size, ensuring in the meanwhile an increasingly high success rate in the resolution of the urolithiasis. The purpose of the study is to review the current role of the ureteroscopy(URS) in the treatment of urinary stones. A non-systematic review was performed considering the most recent Guidelines and results from Literature. The results confirm that, considering ureteral calculi, the stone-free rate (SFR) for URS is significantly higher than for ESWL in the treatment of distal ureteral stones <10 mm and >10 mm. Endoscopy has a first-line role also in the treatment of proximal ureteral stones >10 mm, together with ESWL. Retreatment rate and ancillary procedures are also lower in patients treated with URS, despite it is more invasive if compared with ESWL. Recent data are available in Literature about the treatment of nephrolithiasis with Retrograde Intra-Renal Surgery (RIRS). RIRS is the first-line treatment, together with ESWL, for stones <20 mm, and second choice for stones >20 mm. However, for large renal stones the role of RIRS is still being discussed. In conclusion, the majority of urinary stones can be treated by rigid or flexible URS. Further studies are required to clarify the role of endoscopy in the treatment of large stones, especially if compared to percutaneous approaches.